Regulations on the Use of State Facilities in the Implementation of General Election Campaigns - Fahreza, Mohammad Fadhil; Hufron, Hufron (Universitas PGRI Madiun, 2025)
General elections (Pemilu) play a crucial role in the democratization of politics in Indonesia. As a democratic country, Indonesia adopts a political system based on power that comes from and for the people. becomes a forum for elections where citizens can directly elect their representatives at the national and regional levels. However, the implementation of elections is faced with various challenges, especially related to honest, fair, and transparent implementation. One of the main issues that arises is the scope of state facilities in election campaigns. This study aims to investigate ways of supervision that can prevent the protection of state facilities in election campaigns. The research method used is normative research with an approach to laws, conceptualization, and case studies. The research findings show that effective supervision of the use of state facilities in elections is a crucial step to ensure integrity and fairness in the democratic process. Legal steps and sanctions applied in accordance with the Election Law are expected to reduce violations and maintain the integrity of elections in Indonesia.